OPTIMIZATION, ISOLATION AND CHARACTERIZATION OF BIOACTIVE COMPOUNDS FROM STREPTOMYCES LAVENDULOCOLOR VHB-9 - Bssn, Hima Bindu; Munaganti, Rajesh Kumar; Muvva, Vijayalakshmi; Naragani, Krishna; Indupalli, Mani Deepa (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Optimization, isolation, and characterization of bioactive compounds from Streptomyces lavendulocolor VHB-9 isolated from granite mines of Mudigonda village of Khammam district of Telangana state. Methods: The potent strain was identified as S. lavendulocolor VHB-9 by polyphasic taxonomy. The influence of culture conditions on growth and bioactive compounds production was investigated. Purification of bioactive compounds was done using column chromatography. The structures of the compounds were elucidated on the basis of spectroscopic analysis including Fourier transform infrared, electron spray ionization mass spectrophotometry,1H nuclear magnetic resonance (NMR), and13C NMR. The antimicrobial activity of the compounds produced by the strain was tested against both Gram-positive and Gram-negative bacteria and fungi in terms of minimum inhibitory concentration. Results: Isolation and identification of two compounds, namely (2R, 3R)-2, 3-Butanediol (B1A), and nonadecanoic acid (B1B). Fraction B4 was isolated partially purified fraction and identified by the gas chromatography-mass spectrometry analysis. B1B compound exhibited the highest activity against Bacillus megaterium, Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa, and Candida albicans when compared to B1A and B4 compounds.